2005
DOI: 10.1021/bi051455+
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism at Residue 129 Modulates the Conformational Conversion of the D178N Variant of Human Prion Protein 90−231

Abstract: One of the arguments in favor of the protein-only hypothesis of transmissible spongiform encephalopathies is the link between inherited prion diseases and specific mutations in the PRNP gene. One such mutation (Asp178 → Asn) is associated with two distinct disorders:  fatal familial insomnia or familial Creutzfeldt−Jakob disease, depending upon the presence of Met or Val at position 129, respectively. In this study, we have characterized the biophysical properties of recombinant human prion proteins (huPrP90−2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 53 publications
6
75
0
Order By: Relevance
“…As shown previously (25), incubation of huPrP90-231 under the conditions described in Materials and Methods resulted in time-dependent conversion of the protein to amyloid fibrils that bind thioflavine T dye. Although variable in length, morphologically these fibrils appeared quite homogenous (Fig.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…As shown previously (25), incubation of huPrP90-231 under the conditions described in Materials and Methods resulted in time-dependent conversion of the protein to amyloid fibrils that bind thioflavine T dye. Although variable in length, morphologically these fibrils appeared quite homogenous (Fig.…”
Section: Resultssupporting
confidence: 62%
“…Such long-term protection is typical of a cross ␤-structure, a motif common to many amyloids (27, 31-33, 35, 36). Infrared spectroscopic data indicate that the conversion of PrP23-231 and PrP90-231 to amyloid fibrils is indeed accompanied by a major increase in ␤-structure (24,25). This newly formed ␤-structure is highly unlikely to arise from segments N-terminal to residue Ϸ169, because all peptic fragments derived from this part of PrP90-231 fibrils show very rapid deuterium incorporation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Urea-induced unfolding studies indicated that the thermodynamic stability of PrP decreases by ~22 kJ mol -1 upon introduction of the mutation [136]. It was further found that the structure of D178N PrP Sc is different from WT PrP Sc obtained under the same conditions [137,138].…”
Section: D178nmentioning
confidence: 96%
“…Recently, MD simulation has shown that the mutation of Asp to Asn at position 178 plays an important role in the conformational conversion to -sheet-rich PrP [18]. Linkages between familial prion diseases and mutations in the gene encoding human prion protein were reported and over 20 such mutations have been shown to date to segregate familial CJD, GSS and FFI [1,19,20].…”
Section: Influence Of the Pathogenic Mutations On The Conformational mentioning
confidence: 99%